Pemanfaatan Fitur @AnonymousChat Telegram sebagai Media Kuratif dalam Konseling Kecemasan bagi Remaja dan Dewasa Muda - Fahrezi, Fahmi; Budiyono, Alief; Ijayati, Elis; Chabelita, Vicilia Hellwa (Jurnal Bimbingan dan Konseling Pandohop, 2025)
Anxiety and depression disorders continue to increase among adolescents and young adults due to barriers to accessing traditional counseling services and the associated social stigma. This study aims to explore the role of the @AnonymousChat feature on the Telegram application as an alternative curative medium in counseling interventions. Using a qualitative approach, five participants aged 16–24 years were interviewed in depth to understand their experiences in utilizing the feature. The results revealed that the anonymity of this feature creates a sense of safety that allows users to share without fear of social stigma. However, limitations in deepening communication and emotional openness indicate the need for integration with professional counseling services. This study concludes that the @AnonymousChat feature has the potential as an innovative curative solution, but further development is needed to optimize technology-based mental health support comprehensively.